(untitled) (Journal of the College of Basic Education, 2022)
The induced photodegradation of ethylcellulose (EC) and methylcellulose (MC) films in air was investigated in the presence and absence of benzophenone (BPh) (photosensitizer) by accelerated weathering tester. The addition of (0.2wt %) of benzophenone (BPh) to cellulose derivatives films (25µm in thickness) enhanced the photodegradation of the ethylcellulose (EC) more than methylcellulose (MC) films.The photodegradation rate was followed by increase in carbonyl absorbance of polymers and decomposition rate constant (k d ) of benzophenone in polymers using I.R and U.VVis. spectra respectively. According to the kinetic data and spectra results, the induced photodegradation mechanisms of cellulose derivatives films were suggested under the experimental conditions employed using u.v.radiation at λ = 313 nm , light intensity 3.49*10 5 einsteins.dm 3 .S 1 at temperature 45 o C.